Natural history of Protaetia (Vietnamoprotaetia) sericophora (Seillière) (Coleoptera: Scarabaeidae: Cetoniinae) with notes on collecting flower beetles in karst areas - Zhang, Xin-Yuan; Wen, Hui; Xiong, Ting; Xu, Hao (Zootaxa, 2024)
The natural history of the little-known Protaetia (Vietnamoprotaetia) sericophora (Seillière, 1910) (Coleoptera, Scarabaeidae, Cetoniinae) in China is documented. Records from Guangdong, Guangxi, and Yunnan have significantly extended the distribution range of this species. The female is illustrated for the first time and sexual dimorphism is presented. Photographs of the habitus, parameres, and type materials of this beetle are also provided. The observations on the natural habitat of its larvae provided new insights for capturing the flower beetles occurring in limestone areas and similar habitats.